Otimização topológica de uma prótese transtibial para impressão 3D - LIMA, Fernando Neves (2022)
According to the IBGE, in Brazil, about 24% of the population has some type of physical disability, this disability, in most cases, is linked to the loss of some member of the body. The problems generated by the loss of the limb have been mitigated thanks to technological advances around prostheses, bringing to the amputee a better quality of life and enabling greater autonomy for him. However, the high cost of commercial prostheses has been a barrier to the acquisition of these products, so alternatives to cheapen the manufacturing process using 3D prototyping as an optimization tool becomes relevant, with this the proposal of using printing 3D as a means of manufacturing prostheses. The present work presents the topological optimization process that consists of the search for an optimal distribution of material in a pre-defined design space aiming to minimize or maximize the geometric and mechanical characteristics, applied to the development process of a transtibial prosthesis that will be manufactured via manufacturing. additive (3D printing).